The prefabricated home - Davies, Colin, 1929- (Reaktion Books, 2005)
"Most popular housing is to some extent prefabricated and has been for more than a hundred years. This is one of the reasons why it does not really count as architecture." "Architects are good at designing prototypes for prefabricated houses, but bad at following through with volume production. If they want to succeed in this field, and make a real difference to most people's most intimate experience of buildings, then they must be prepared to learn from areas of the building industry that they have traditionally shunned, from pattern-book houses to modular hotels, from Portakabins to park homes. This book will be of interest to architects, architecture students and anyone connected with the building industry, but its jargon-free discussion of historical, theoretical and practical questions is designed to appeal to anyone who has ever lived in an ordinary house."--Jacket.